Role of Temperate Bacteriophage ϕ20617 on Streptococcus thermophilus DSM 20617T Autolysis and Biology - Arioli, Stefania; Eraclio, Giovanni; Della Scala, Giulia; Neri, Eros; Colombo, Stefano; Scaloni, Andrea; Fortina, Maria Grazia; Mora, Diego (Frontiers in Microbiology, 2018)
Streptococcus thermophilus DSM 20167T showed autolytic behavior when cultured in lactose- and sucrose-limited conditions. The amount of cell lysis induced was inversely related to the energetic status of the cells, as demonstrated by exposing cells to membrane-uncoupling and glycolysis inhibitors. Genome sequence analysis of strain DSM 20617T revealed the presence of a pac-type temperate bacteriophage, designated Φ20617, whose genomic organization and structure resemble those of temperate streptococcal bacteriophages. The prophage integrated at the 3'-end of the gene encoding the glycolytic enzyme enolase (eno), between eno and the lipoteichoic acid synthase-encoding gene ltaS, affecting their transcription. Comparative experiments conducted on the wild-type strain and a phage-cured derivative strain revealed that the cell-wall integrity of the lysogenic strain was compromised even in the absence of detectable cell lysis. More importantly, adhesion to solid surfaces and heat resistance were significantly higher in the lysogenic strain than in the phage-cured derivative. The characterization of the phenotype of a lysogenic S. thermophilus and its phage-cured derivative is relevant to understanding the ecological constraints that drive the stable association between a temperate phage and its bacterial host.